Closed-loop control of product properties in metal forming. Issue 2 (2016) - Allwood, J.M.; Duncan, S.R.; Cao, J.; Groche, P.; Hirt, G.; Kinsey, B.; Kuboki, T.; Liewald, M.; Sterzing, A.; Tekkaya, A.E.
Abstract: Metal forming processes operate in conditions of uncertainty due to parameter variation and imperfect understanding. This uncertainty leads to a degradation of product properties from customer specifications, which can be reduced by the use of closed-loop control. A framework of analysis is presented for understanding closed-loop control in metal forming, allowing an assessment of current and future developments in actuators, sensors and models. This leads to a survey of current and emerging applications across a broad spectrum of metal forming processes, and a discussion of likely developments.